Vaughan Kyle, Penny Kyle and Keith Burns interviewed by Rob Willis for the Rob and Olya Willis folklore collection - Kyle, Vaughan, 1925-2011.; Willis, Rob, 1944-; Cameron, Bruce, 1953-; Kyle, Penny, 1947-; Burns, Keith, 1932- (2002)
Folkloric recording. Vaughan Kyle, Penny Kyle and Keith Burns play folk music and talk about their musical backgrounds.
This is another recording on the folklore of the Nulla (Nulla Nulla) an isolated area near Kempsey, N.S.W. Vaughan Kyle learnt the fiddle at an early age from his Uncle George Kyle, one of a family of four fiddlers. Vaughan talks about the early days, music of the area and plays some of the older tunes on the fiddle. He talks about Aboriginal musicians on the Nulla; main instruments played in the district were fiddle & accordion; regular dances at Bellbrook & in the houses; early band days, playing with Tommy Rainbow. Penny recalls her family background in Kempsey, N.S.W.; learning to play the fiddle from George Kyle. Keith, born at Port Macquarie recalls his family's musical background; first instrument played being the piano accordion.
Tape 2 continued Music: Maple leaf waltz -- Waltz (unidentified) -- Malpe sugar time -- Old fiddler Joe (solo fiddle) -- Girl I left behind -- The lone fiddler (from Slim Dusty) -- Springtime in the valley -- Unidentified tune -- Click go the shears/Ring the bell watchman -- Redwing -- Varsovienna -- Gonzales schottische.
Recorded with Bruce Cameron.
Recorded on Aug. 12, 2002 at South West Rocks, (N.S.W.)
Digital master available
National Library of Australia Oral History & Indigenous Programs collection at ORAL TRC 6936/53.
National Library of Australia Oral History & Indigenous Programs collection at ORAL TRC 6936/58.
Timed summary (3 p.)
Keywords: Kyle, Vaughan, -- 1925-2011 -- Interviews; Kyle, Penny, -- 1947- -- Interviews; Burns, Keith, -- 1932- -- Interviews; Folk musicians -- New South Wales -- South West Rocks -- Interviews; Folklore -- New South Wales -- Nulla Nulla; Folk music -- New South Wales -- Nulla Nulla; Folk musicians -- New South Wales -- Nulla Nulla -- Interviews; Aboriginal Australians -- Songs and music -- New South Wales -- Nulla Nulla; Folklore -- New South Wales -- Nulla Nulla; Folk musicians